On Semi-p-Compact Space1 (Baghdad Science Journal, 2025)
The purpose of this paper is to introduce a new type of compact spaces, namely semi-p-compact spaces which are stronger than compact spaces; we give properties and characterizations of semi-p-compact spaces.